The effects of suspended weight resistance training on agility in collegiate athletes - Christensen, B.; Thielen, S.; Hackney, K.; Moen, J. (ISBS Proceedings Archive (Michigan), 2018)
Instability resistance training techniques are commonly used to increase athletic performance. The purpose of this study was to analyze the effects of performing the squat exercise with suspended weight within a six-week resistance training program on agility in collegiate male athletes. Thirty-two male collegiate baseball players were randomly assigned to a suspended or conventional resistance training group. They completed the T-test agility test before and after a six-week resistance training program. The suspended group had weight plates hanging below the barbell for the squat exercise. A repeated measures ANOVA was used to assess improvements in performance within groups and between groups. The T-test agility times for both groups significantly decreased from pre- to post-testing, but there were no significant differences between groups.